Do Black Lives Really Matter—To Social Work? Introduction to the Special Edition. (March 2018) - Holosko, Michael J.; Briggs, Harold E.; Miller, Keva M.
This article presents and summarizes the special issue entitled: Practice, Research, and Scholarship on African American . The authors examine the professions' contradictory actions in partnering with African American scholars, communities, and people to achieve its social justice and civil rights mission. It reintroduces the reader of this collection to June Gary Hopps who originally rung the clarion call to action about the profession's waffling nature regarding African Americans. The authors overview the collection, which depicts the professions' lack of focus on issues of race, African American well-being, and oppression experiences. This issue unravels the role played by social work in its meager attention to the plight of African American leaders and faculty, their achievements, and challenges. It also conveys the realities of too few research studies on key issues impacting African Americans. This article concludes with a nudge to the reader to weigh the evidence contained in this serial.